Mapping the world the story of cartography - Riffenburgh, Beau (Andre Deutsch Limited, 2014)
Mapping the World takes you on a journey through the history of cartography and is essentially a history of the world and how its territories were discovered and explored. Maps have been an integral part of the way humans have lived for approximately 8,000 years. The first accurate maps were produced in Ancient Babylonia. The earliest world map is the Babylonian World Map, which is symbolic and not an exact representation. It deliberately doesn't include the Persians or the Egyptians. The Ancient Greeks also produced maps, although they were mostly imaginary reconstructions of the world. Maps have been crucial in the development of empires, have helped to win wars, and have encouraged man to venture further than his or her known boundaries. Beautifully illustrated, The Men Who Mapped the World is a fascinating look at how the science of cartography developed, how maps are used not just for getting from A to B, and why cartography is so important to our history of the world and the world we live in. Nowadays, we take the use of Sat Nav and Google maps for granted, but this book reflects on the fact that it all began with human imagination and the desire for knowledge.